Pemanfaatan Laboratorium Virtual Terhadap Pembelajaran Siswa dengan Keterbatasan Fisik: Tinjauan Literatur - Baiq Ziadatu Rahmah; Aqirully Ramadhani; Alya Rizkika; Gunawan Gunawan; Nina Nisrina (Indonesian Journal of Teacher Education, 2023)
Science learning requires practical activities as a means of concretely understanding concepts. However, students with disabilities often face obstacles in accessing conventional laboratories. This study aims to examine the use of virtual laboratories for learning for students with disabilities through a literature review. Twelve scientific articles published between 2014 and June 2023 were analyzed based on inclusion criteria, including topic relevance, research type, and relevance to inclusive learning. The literature selection process involved identification, screening, and eligibility. Data were analyzed using a qualitative thematic analysis approach. The study results indicate that virtual laboratories can improve student accessibility, participation, conceptual understanding, and learning independence. Furthermore, flexibility and security are key advantages in supporting inclusive learning. However, challenges remain, such as limited infrastructure and digital literacy.